2023
DOI: 10.3390/healthcare11091221
|View full text |Cite
|
Sign up to set email alerts
|

Combined Rehabilitation Protocol in the Treatment of Osteoarthritis of the Knee: Comparative Study of Extremely Low-Frequency Magnetic Fields and Soft Elastic Knee Brace Effect

Abstract: The investigation of this observational case–control study aimed at determining the effectiveness of a combined treatment of extremely low-frequency electromagnetic fields (ELF) with a soft elastic knee brace versus ELF alone in knee osteoarthritis (KOA) with respect to a reduction in pain and functional recovery. We hypothesized that the combined use of ELF and a soft elastic knee brace may provide better results. Thirty-five patients (N = 35, divided into Group 1 = ELF and Group 2 = ELF with the soft elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…The authors concluded that non-invasive PEMFs therapy can have a significant and rapid impact on pain from early knee osteoarthritis [49]. Similar results were also obtained by other authors [50][51][52].…”
Section: Joint Preservationsupporting
confidence: 79%
“…The authors concluded that non-invasive PEMFs therapy can have a significant and rapid impact on pain from early knee osteoarthritis [49]. Similar results were also obtained by other authors [50][51][52].…”
Section: Joint Preservationsupporting
confidence: 79%
“…In the study by S. Masiero et al (2020), all patients (diagnosis of osteoarthritis, neck/back pain, or tendinopathies) underwent ten sessions of percutaneous short-wave diathermy, three times/week, with each session lasting 15–20 min, and using frequencies of 4 or 8 MHz and a heat intensity between 40 and 60 W. The authors suggest that the data reported a positive trend in reducing musculoskeletal pain in the short term [ 24 ]. Also, ultrasound waves of 1 MHz frequency were applied for 5 min to the target knee, as was direct current for 10 min for 10 treatment sessions together with 0.4% Dexamethasone sodium phosphate (DEX-P) phonophoresis (PH), with 0.4% DEX-P iontophoresis (ION) therapy compared: both therapeutic modalities were found to be effective and generally well tolerated after 10 treatment sessions [ 18 , 25 ]. In low-grade KOA patients according to the Kellgren–Lawrence classification, six sessions of pulsed electromagnetic field therapy (PEMFT) resulting in significantly better results than low-level laser therapy (LLLT) and an immediate positive effect on pain and physical function [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed for a balanced sample size across treatment levels (sham, extensive, and intensive) while considering outpatient pain levels. Considering a 10% dropout rate [ 18 ], with 54 valid outpatients, potentially 48.6 would remain after dropouts, split equally into three groups (16.2 per group). We opted for a 2:1 ratio between treated and control groups.…”
Section: Methodsmentioning
confidence: 99%